Meningkatkan Kinerja Organisasi Melalui Komunikasi Efektif - Faza Fil Khaunaini, Muhamad; Arroyyani , Putri; Lailatul Komariyah , Nur; Ellyana , Anis; Mu’Alimin (Idarotuna : Journal of Administrative Science, 2024)
Improving organizational performance can be achieved through effective communication. In an effort to evaluate the relationship between organizational performance and effective communication, this research examines relevan t literature. The research was conducted by analyzing fifteen related articles from various sources. The results of the analysis show that effective communication helps in achieving organizational goals, productivity, work quality and motivation. Additionally, things like the work environment and organizational culture influence the relationship between communication and performance. However, challenges such as differences in perception, physical barriers, semantic barriers and psychological barriers can interfere with effective communication. A better understanding of communication methods, communication skills and communication environment can improve organizational performance. Based on the literature data, further research is needed regarding communication patterns, communication skills and communication climate. Organizations also need to overcome communication barriers and encourage changes in the way they communicate.